The Galactic bulge exploration - IV. RR Lyrae stars as tracers of the Galactic bar: 3D and 5D analysis and extinction variation - Prudil, Zdeněk; Kunder, A.; Beraldo e Silva, L.; Gough-Kelly, S.; Rejkuba, M.; Anderson, S. R.; Debattista, V. P.; Gerhard, O.; Rich, R. M.; Nataf, D. M.; Koch-Hansen, Andreas; Savino, A.; et al. (Astronomy and astrophysics, 2025)
RR Lyrae stars toward the Galactic bulge are used to investigate whether this old stellar population traces the Galactic bar. Although the bar is known to dominate the mass in the inner Galaxy, there is no consensus on whether the RR Lyrae star population, which constitutes some of the most ancient stars in the bulge and thus traces the earliest epochs of star formation, contributes to the barred bulge. We create new reddening maps and derive new extinction laws from visual to near-infrared passbands using improved RR Lyrae period-absolute magnitude-metallicity relations, enabling distance estimates for individual bulge RR Lyrae variables. The extinction law is most uniform in and and the distances to individual RR Lyrae based on these colors are determined with an accuracy of 6 and 4%, respectively. Using only the near-infrared passbands for distance estimation, we infer the distance to the Galactic center equal to pc after geometrical correction. We show that variations in the extinction law toward the Galactic bulge can mimic a barred spatial distribution in the bulge RR Lyrae star population in visual passbands. This arises from a gradient in extinction differences along Galactic longitudes and latitudes, which can create the perception of the Galactic bar, particularly when using visual passband-based distances. A barred angle in the RR Lyrae spatial distribution disappears when near-infrared passband-based distances are used, as well as when reddening law variations are incorporated in visual passband-based distances. The prominence of the bar, traced by RR Lyrae stars, depends on their metallicity, with metal-poor RR Lyrae stars ([Fe/H] < −1.0 dex) showing little to no tilt with respect to the bar. Metal-rich ([Fe/H] > −1.0 dex) RR Lyrae stars do show a barred bulge signature in spatial properties derived using near-infrared distances, with an angle of ι = 18 ± 5 deg, consistent with previous bar measurements from the literature. This also hints at a younger age for this RR Lyrae subgroup. The 5D kinematic analysis, primarily based on transverse velocities, indicates a rotational lag in RR Lyrae stars compared to red clump giants. Despite variations in the extinction law, our kinematic conclusions are robust across different distance estimation methods.